Training on Village History Digitalisation: Cultural Preservation and Strengthening Love for the Homeland for the Community of Cangaan Village, Kanor Subdistrict, Bojonegoro Regency - Giati Anisah; Nurul Huda; Rafi Ajrul Baha' Udin (Universitas Veteran Bangun Nusantara, 2025)
This community service program aims to address the threat of cultural erosion and the generational gap in accessing local history in Cangaan Village, Bojonegoro Regency. The initiative focuses on digitizing the village's historical and cultural heritage through community empowerment and digital literacy training. The methods employed include Focus Group Discussions (FGD) to map assets, intensive training on documentation techniques, content creation, and digital archiving, followed by the practical application of building a digital repository. The partners in this activity were the Cangaan Village Government and the local youth organization, who were actively involved in data collection and content management. The program's success was measured by a significant increase in post-test scores compared to pre-test results, indicating improved understanding and digital skills among participants. Furthermore, the output includes tangible digital products such as e-books, articles, short documentary videos, and a structured digital archive. The results demonstrate that this digitization effort effectively preserves cultural assets, strengthens local identity and love for the homeland, and enhances the digital literacy of the community. This project ensures short-term sustainability through the transfer of knowledge to the youth and long-term sustainability by integrating the digital content into local education and tourism promotion.